2018
DOI: 10.3390/ijms19020423
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Humoral IL-6 Cytokine in Mediating Pro-Inflammatory Endothelial Cell Response in Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a multifactorial disease with limited therapeutic options. Numerous intrinsic and extrinsic factors are involved in ALS motor neuron degeneration. One possible effector accelerating motor neuron death in ALS is damage to the blood-Central Nervous System barrier (B-CNS-B), mainly due to endothelial cell (EC) degeneration. Although mechanisms of EC damage in ALS are still unknown, vascular impairment may be initiated by various humoral inflammatory factors and other mediato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 145 publications
1
25
0
2
Order By: Relevance
“…One study suggested that this was a response to hypoxia rather than to the disease itself (137) (see below). IL-6 has been suggested to have a role in endothelial damage in ALS (138). Genetic variation in the IL-6 receptor has been shown to modify the severity of ALS (88).…”
Section: Interleukin 6 (Il-6)mentioning
confidence: 99%
“…One study suggested that this was a response to hypoxia rather than to the disease itself (137) (see below). IL-6 has been suggested to have a role in endothelial damage in ALS (138). Genetic variation in the IL-6 receptor has been shown to modify the severity of ALS (88).…”
Section: Interleukin 6 (Il-6)mentioning
confidence: 99%
“…Additionally, TREM 2 is also overexpressed and correlates negatively with patient’s prognosis, being a potential biomarker for the disease (Cady et al, 2014 ). Activated microglia can induce oxidative stress via ROS and NO and proinflammatory cytokines such as TNF-α, IL-6, and IL-1β, which induce MN cell death (Garbuzova-Davis et al, 2018 ). These cytokines activate astrocytes, which also affect ALS onset and development by two different approaches.…”
Section: Neuroinflammation In Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…La IL-6 es una citoquina bifuncional que media actividades pro y antiinflamatorias. Esta citoquina es expresada por neutrófilos y eosinófilos no estimulados, linfocitos B y T, monocitos y células endoteliales estimuladas (Garbuzova-Davis et al 2018). En los cultivos tratados con FLt y FFv se evidenció la producción de IL-6 (p>0.05).…”
Section: Figuraunclassified